P-stereogenic centre via Pd/Cu-bimetallic catalytic selective phosphinylation of allenylic acetates - Gen Li; Shichao Hong; Xuechen Li; Wenhao Zhao; Chaobo Ye; Yi Yu; Huajie Jiang; Jie Yu; Xue Zhang; Shengming Ma; Qiankun Li (Nature Communications)
Abstract P-stereogenic organophosphorus compounds are a class of highly important compounds due to their potentials in asymmetric catalysis both as ligands or catalysts and medicinal chemistry. Herein, we report an efficient protocol under bimetallic catalysis of Pd/Cu for highly regio-, E- and enantioselective phosphinylation of allenylic acetates with racemic secondary phosphine oxides forming a wide range of versatile P-stereogenic 1,3-dienyl phosphine oxides with 86–95% ee. The regioselectivity is unique as compared to the traditional catalytic enantioselective allenylations.